The influence of online customer rating, online customer review and taglines “free shipping” on purchasing decisions at the shopee marketplace in Cikarang - Zed, Etty Zuliawati; Pupung Purnamasari; Sesri Sellina (Jurnal Ekonomi, 2024)
The purpose of this study was to analyse the effect of each independent variable: online customer rating, online customer review and "free shipping" tagline on purchasing decisions. The population in this study were Shopee marketplace users in Cikarang City with a sample of 100 respondents determined using purposive sampling. The data analysed were primary data collected by questionnaire. Based on SPSS version 25.0 data processing, the results show that the research instrument test shows that all indicators are valid and all variables are reliable. Based on the F test simultaneously all independent variables have an effect on purchasing decisions. Based on the results of the regression coefficient and t test, it shows that the online customer rating variable has a positive and significant effect on purchasing decisions, the online customer review variable has a positive and significant effect on purchasing decisions and the "free shipping" tagline variable has a positive and significant effect on purchasing decisions.